Psychomimesis: LSD and Disability Immersion Experiences of Schizophrenia - Donaldson, Elizabeth J. (Disability Studies Quarterly, 2012)
Before LSD became infamous as a psychedelic in the late 1960s, it had an earlier career as a psychotomimetic--a drug which could produce a “model psychosis” or “artificial schizophrenia.” This paper focuses on the use of LSD in psychiatry in this often overshadowed period. I examine experiments that use LSD as a prosthetic tool to produce “disability immersion” experiences of schizophrenia in people without psychiatric symptoms or diagnoses. This use of LSD reversed the traditional way drugs circulate in psychiatry: instead of patients receiving mind-altering medication to ameliorate disabling psychiatric symptoms, mental health professionals took LSD to temporarily disable their normal cognition. Despite the problematic nature of disability immersion experiences in general and the negative valence often attached to mental illness in these accounts, these trips into madness produced, I will argue, positive therapeutic insights, perhaps best illustrated by architect Kiyo Izumi’s LSD-inspired design for Yorkton Psychiatric Centre. Keywords: schizophrenia, mental illness, psychiatry, disability simulation, LSD